2019
DOI: 10.3390/rs11242910
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Air Pollution in China Inferred from Changes between Satellite-Based and Measured Surface Solar Radiation

Abstract: The air pollution crisis in China has become a global concern due to its profound effects on the global environment and human health. To significantly improve the air quality, mandatory reductions were imposed on pollution emissions and energy consumption within the framework of the 11th and 12th Five Year Plans of China. This study takes the first step to quantify the implications of recent pollution control efforts for surface solar radiation (SSR), the primary energy source for our planet. The observed bias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 66 publications
1
8
0
Order By: Relevance
“…These studies suggest the major role of vehicular traffic in air quality control. While government pollution control policies appear to have improved air quality in Beijing and Tianjin [5][6][7], pervasive pollution is still evident across a much larger surrounding region, as demonstrated by Yuan and Yang's [8] report of significant worsening in other cities of the BTH region.…”
Section: Introductionmentioning
confidence: 99%
“…These studies suggest the major role of vehicular traffic in air quality control. While government pollution control policies appear to have improved air quality in Beijing and Tianjin [5][6][7], pervasive pollution is still evident across a much larger surrounding region, as demonstrated by Yuan and Yang's [8] report of significant worsening in other cities of the BTH region.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with the global trend, a similar transition has been widely reported in the R trend of China with the estimated changing rates of −2.5 to −12 and 0.4 to 4 W m −2 decade −1 during the global dimming and brightening phases, respectively (Wang & Yang, ). Based on homogeneous data, recent studies further updated the decadal variations of R in China into three stages: a dimming until 1990, a leveling off afterward, and an actual brightening since 2008 (Wang, Trentmann et al, ; Yang et al, , ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies show that the Rs in China showed significant decline trends before the 1980s by 2 to 8 Wm −2 per decade [25][26][27][28][29][30][31][32], which did not persist into the 1990s. However, the magnitudes of variations in Rs were still controversial.…”
Section: Decadal Variationsmentioning
confidence: 92%